A capability maturity framework for knowledge transfer. Issue 4 (August 2018) - Scanlan, John
Knowledge transfer (KT) activity at a research performing organization (RPO) is usually reported as a set of metrics arising from the RPO's research and engagement, such as links to industry, intellectual property creation, licensing of new technology and new start-up company creation. However, these basic metric sets are not very effective, either from the point of view of benchmarking or as measures of quality. To address this inadequacy, the author has developed and implemented a 'knowledge transfer capability maturity framework', which attempts to capture the essentials of good-quality management across key KT processes, providing for the identification of deficiencies and subsequent improvements. This article also presents the use of the ratios of currently reported metrics as an additional and helpful benchmarking tool, and the possible use of these ratios as a means of quantifying the quality measurement of the capability maturity framework presented.